Training Product-Unit Neural Networks with Cuckoo Optimization Algorithm for Classification - Kahramanli, Humar (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In this study Product-Unit Neural Networks (PUNN) which is the special class of feed-forward neural network, has been trained using Cuckoo Optimization algorithm. The trained model has been applied to two classification problem. BUPA liver disorders and Habermans Survival Data have been used for application. The both data have been obtained from UCI machine Learning Repository. For comparison Backpropagation (BP) and LevenbergâMarquardt (LM) algorithms have been used. The application results show that the PUNN trained with Cuckoo Optimization algorithm is achieved better classification accuracy.